Concepção e desenvolvimento de um sistema eletrônico baseado em diodos emissores de luz para simulação de espectro - Martin, Klaus Tesser (2017)
This master thesis presents the conception and development of a lighting system based on lighting emitting diodes (LEDs) capable of accurately reproducing light spectra. The main motivation of this work is the development of a lighting system capable of simulating the spectrum of natural sunlight under different climatic conditions for application in studies of plant physiology LEDs are used due their characteristics of narrowband light emission, low power consumption, reduced volume, long lifetime, easily modulated light emission and solid-state electronics. With an increasing selection of LEDs with different spectral distribuition available on the market, multiple LEDs with different dominant wavelengths can be combined, and the flux emitted by each of them can be individually controlled, thus allowing spectral emulation. The problem in determining the optimized combination of LEDs that results in the spectrum closest to the reference was modeled as a Mixed Integer Programming (MIP) problem. The LEDs selected through the optimization procedure were driven by a driver composed of Buck converters with hysteresis control and pulse width modulation (PWM) light intensity control. After spectral measurements were performed on the developed LED module, it was concluded that the proposed system is able to reproduce light spectra with fidelity.